THE INFLUENCE OF SOCIAL MEDIA MARKETING, BRAND IMAGE, AND PRODUCT QUALITY ON REPURCHASE INTENTION(A CUSTOMER STUDY: ARJ88 STORE IN DENPASAR CITY) - Dzikrul Akbar Bayuadi; Ni Wayan Ekawati, I Gusti Made Suwandana (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to analyze the effect of social media marketing, brand image, and product quality on repurchase intention. The research was conducted on customers of Arj88 Store in Denpasar City, with a sample of 100 respondents. The sampling method used in this study is purposive sampling. Data collection was carried out by distributing offline questionnaires to the respondents. Data analysis in this study employed multiple regression analysis. The results of the study indicate that social media marketing, brand image, and product quality have a positive and significant effect on repurchase intention, both partially and simultaneously.